PENGELOLAAN EKOWISATA MANGROVE DI KAWASAN WISATA MANGROVE DESA GAMPONG BARO KECAMATAN SETIA BAKTI KABUPATEN ACEH JAYA - Summi Elfandayani; Mira Mauliza Rahmi; Friyuanita Lubis; Nabil Zurba; Mai Suriani (Journal of Aceh Aquatic Sciences, 2021)
Mangrove ecotourism is an environmentally friendly tourism object where the tourism prioritizes aspects of the natural beauty of the mangrove forest and the fauna that live around it without destroying it. Ecotourism is a form of tourism that is responsible for the preservation of natural areas, provides economic benefits and maintains the cultural integrity of the local community (Fandeli, 2000). Management of ecosystem mangrove is very important to maintain and preserve the mangrove ecosystem. The purpose of the study was to determine the ecotourism potential that exists in the Aceh Jaya Mangrove Ecotourism Area and to determine the ecotourism management strategy in the Aceh Jaya Mangrove Ecotourism Area. This research is important to do to find how to management of ecosystem mangrove in Aceh Jaya in tourism mangrove area of developing ecotourism areas so that mangrove ecotourism can develop at this time. Aceh Jaya District has a mangrove area of 500 hectares. Mangrove ecotourism has enormous potential to be developed into a tourist spot because it has six types of mangroves including Rhizopora mukronata, Rhizopora apiculata, Rhizopora stylosa, Bruguiera cylindrical, Bruguiera gymnorhiza, and Nypah fruticans. There are mainland fauna such as birds, monitor lizards, lizards, snakes, and monkeys, as well as aquatic fauna of long-snout swordfish, sepat fish, slugs, oysters, crabs, and shellfish. Mangrove ecotourism in Aceh Jaya has been used for various purposes such as for research, providing job opportunities for local communities and as a source of livelihood for local communities. The community-based management strategy of the Aceh Jaya mangrove ecotourism area means involving the community in the planning, implementation, and management of ecotourism businesses in all activities carried out. Mangrove ecotourism has 2 small boats, libraries, trekking (bridges), mangrove nursery houses and tour guides who are responsible for providing instructions, companions and serving tourists.